Laparoscopic Versus Finger-Assisted Open Donor Nephrectomy Techniques: A Safe Alternative. (July 2018) - Shahbazov, Rauf; Maluf, Daniel; Azari, Feredun; Hakim, David; Martin, Oscar; Dicocco, Pierpoalo; Alejo, Jennifer; Saracino, Giovanna; Hakim, Nadey
Abstract : Background: Advances in minimally invasive surgery for live kidney donor nephrectomy have led to the use of the laparoscopic and robotic technique as the standard of care. The aim of the study was to compare an open finger-assisted open donor nephrectomy (FAODN) versus standard laparoscopic donor nephrectomy (LDN). Methods: Retrospective demographic and surgical data were analyzed using the electronic medical records at the University of Virginia and Imperial College Hospital. The analysis included 95 consecutive donors in each center undergoing donor nephrectomy. LDN and FAODN were compared using Fishers Exact Test and Likelihood Ratio Chi-Square. Results: Overall, donor demographics and clinical characteristics were similar between groups. The FAODN group had less females donors (70.5% vs. 29.5%, p=0.003) with similar median body mass index (BMI) (28 vs. 26, p=0.032). The LDN group had longer operative duration (3.5 vs. 1.2 hours, p<0.001), longer combined length of incision (6 vs. 5 cm. p=0.001), with shorter median hospital length of stay (LOS) (3 vs. 4 days, p<0.001). Left nephrectomy was preferred in both groups. Minor postoperative complications occurred less often in the FAODN group (14.7% vs. 31.6%, p=0.0094) while rates of hernia, operative blood transfusions and postoperative bleeding episodes were similar between groups. Recipients of LDN donors demonstrated a higher creatinine (1.1 vs. 0.9 mg/dl, p<0.001), and lower recipient GFR at 1 year (60 vs. 89 ml/min/1.73m2, p<0.001) post-donation. Conclusions: Our study demonstrates that FAODN is a successful alternative to LDN. It appears to provide kidney donors with favorable outcomes in terms of complications and outcomes, and recipients with excellent renal function at 1 year post-donation.